EFEKTIFITAS RUMPUT LAUT UNTUK PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL - Untari Anggeni; Tri Sundari, Dona; Rohani; Nurbaity (Jurnal Kesehatan dan Pembangunan, 2024)
The gestation period starts from conception to the birth of the fetus. Normal pregnancy duration is 280 days (40 weeks) counting from the first day of the last menstruation. Anemia is more common in pregnancy, this is because during pregnancy the need for nutrients increases and changes occur in the blood and bone marrow. Seaweed (sea weed) is a macroscopic chlorophyll-sized thallus plant and scientifically known as algae. Seaweed is a rich source of minerals, protein vitamins, carbohydrates with very little fat content. This study used a literature review, namely a series of studies related to methods of collecting library data or research whose research objects were explored through a variety of library information (books, encyclopedias, scientific journals, newspapers, magazines and newspapers). Based on the results of the literature review, it is known that Eucheuma sp. seaweed is a food ingredient that contains several intermediate compounds needed in the synthesis of hemoglobin such as iron, protein and vitamin B complex. Eucheuma sp. is also a seaweed that can stabilize the number of blood cells. red blood cells, white blood cells and hemoglobin. so it is effective for increasing hemoglobin levels in pregnant women. With this research, it is hoped that it can add insight for pregnant women to increase awareness of anemia in pregnant women. Eucheuma sp is also a seaweed that can stabilize the number of red blood cells, white blood cells, and hemoglobin. so it is effective for increasing hemoglobin levels in pregnant women. With this research, it is hoped that it can add insight for pregnant women to increase awareness of anemia in pregnant women. Eucheuma sp is also a seaweed that can stabilize the number of red blood cells, white blood cells, and hemoglobin. so it is effective for increasing hemoglobin levels in pregnant women. With this research, it is hoped that it can add insight for pregnant women to increase awareness of anemia in pregnant women